2016
DOI: 10.1371/journal.pone.0146643
|View full text |Cite
|
Sign up to set email alerts
|

Human Gut Bacteria Are Sensitive to Melatonin and Express Endogenous Circadian Rhythmicity

Abstract: Circadian rhythms are fundamental properties of most eukaryotes, but evidence of biological clocks that drive these rhythms in prokaryotes has been restricted to Cyanobacteria. In vertebrates, the gastrointestinal system expresses circadian patterns of gene expression, motility and secretion in vivo and in vitro, and recent studies suggest that the enteric microbiome is regulated by the host’s circadian clock. However, it is not clear how the host’s clock regulates the microbiome. Here, we demonstrate at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
188
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(204 citation statements)
references
References 46 publications
11
188
1
4
Order By: Relevance
“…A potential role for gut-secreted melatonin in passing circadian timing cues from host to commensal bacteria was presented by Jiffin Paulose from Dr. Cassone’s laboratory. Melatonin increased motility and swarming in Enterobacter aerogenes, an effect that is at least partially mediated by melatonin receptors 11 .…”
Section: Circadian Dysrhythmia In Gi Diseasesmentioning
confidence: 98%
“…A potential role for gut-secreted melatonin in passing circadian timing cues from host to commensal bacteria was presented by Jiffin Paulose from Dr. Cassone’s laboratory. Melatonin increased motility and swarming in Enterobacter aerogenes, an effect that is at least partially mediated by melatonin receptors 11 .…”
Section: Circadian Dysrhythmia In Gi Diseasesmentioning
confidence: 98%
“…Another is to request a routine sample at a prescribed time of day – an option which preliminary work in our laboratory indicates is feasible [ unpublished data ]. The frequency and timing of collection is especially important in light of recent findings suggesting diurnal rhythms in certain gut microbes, and sensitivity to melatonin [6]. Future studies will need to determine the sensitivity of samples to time of day in order to establish best practice in timing and frequency of sample collection.…”
mentioning
confidence: 99%
“…Then, 16S RNA sequencing revealed that, compared with the 12 h dark/12 h light cohort, there were much fewer observed species of enteric bacteria in the other two groups (Figure 1E). Given that gut microbiota is sensitive to melatonin [14], we assesses the expression of Mtnr1a and Mtnr1b , the receptors of melatonin, at different circadian times. Intriguingly, the expression of Mtnr1a and Mtnr1b was different among the three cohorts (Figure 1F,G), suggesting that the alteration of intestinal microbiota might depend on circadian rhythm-shaped expression of Mtnr1a and Mtnr1b .…”
Section: Resultsmentioning
confidence: 99%